Oxalis bifurcatifolia (O. sect. Carnosae, Oxalidaceae), a new succulent species endemic to the Atacama Desert, Chile - Cádiz-Véliz Arón; Casale, Jean-François (Phytotaxa, 2026)
The Atacama Desert in northern Chile is one of the oldest and driest desert ecosystems on the planet and harbors a flora characterized by high levels of endemism and key adaptations such as succulence. Within this flora, Oxalis is among the most diverse genera, and Chile represents an important center of diversification, particularly for section Carnosae, distinguished by unequal sepals, pachycaulous stems, succulent leaves, and thickened roots. Here we describe Oxalis bifurcatifolia, a new succulent species of O. sect. Carnosae endemic to the coastal desert of the Atacama Region, discovered during fieldwork carried out in a Desierto Florido event in 2025. The species differs from morphologically similar taxa—particularly O. tortuosa, O. novemfoliolata, O. ovalleana, and O. leucophylla—by a combination of traits including trifoliolate leaves with obtriangular leaflets, a deeply emarginate apex forming two long bifurcate lobes, markedly larger sepals, and dichasial cymes with strongly contracted cincinni internodes that produce an umbel-like inflorescence. Oxalis bifurcatifolia inhabits open xerophytic scrublands influenced by coastal fog, within a narrow altitudinal belt between 200–870 m a.s.l. and is currently known only from three localities situated outside protected areas. Because of its extremely restricted distribution, low number of known populations, and exposure to threats such as mining activities, livestock grazing, and road construction, the species is assessed as Endangered (EN) under IUCN criterion B2ab(iii). A detailed morphological description, distribution map, photographic material, and an updated key to the Chilean species of O. sect. Carnosae are provided.